1991
DOI: 10.1126/science.252.5009.1167
|View full text |Cite
|
Sign up to set email alerts
|

Arginine-Mediated RNA Recognition: the Arginine Fork

Abstract: Short peptides that contain the basic region of the HIV-1 Tat protein bind specifically to a bulged region in TAR RNA. A peptide that contained nine arginines (R9) also bound specifically to TAR, and a mutant Tat protein that contained R9 was fully active for transactivation. In contrast, a peptide that contained nine lysines (K9) bound TAR poorly and the corresponding protein gave only marginal activity. By starting with the K9 mutant and replacing lysine residues with arginines, a single arginine was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
558
1
7

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 663 publications
(588 citation statements)
references
References 29 publications
22
558
1
7
Order By: Relevance
“…The mobility of U23, U38, and U40 decreased while U25 became more mobile, resulting in a dynamic signature similar to that previously obtained for argininamide (23), which has been observed to bind TAR through its guanidino group (28,29).…”
Section: Multicyclic Dyessupporting
confidence: 76%
“…The mobility of U23, U38, and U40 decreased while U25 became more mobile, resulting in a dynamic signature similar to that previously obtained for argininamide (23), which has been observed to bind TAR through its guanidino group (28,29).…”
Section: Multicyclic Dyessupporting
confidence: 76%
“…Tat is a key regulatory protein as it enhances the expression of all viral genes, and the virus is not able to replicate in the absence of Tat. Tat binds to the uridine-rich bulge of TAR [14] and the core and the basic region of Tat are the key elements for specific recognition of TAR [5][6][7][8][9][10]. Structural studies of the Tat TAR interaction have shown conformational changes in TAR on binding of various Tat peptides [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Tat contains an arginine-rich motif (ARM) in which a single arginine residue has been shown by biochemical and in vivo transactivation assays to bind to the TAR bulge region. 17,18 Several NMR studies have elucidated the major conformational transition that argininamide (a tight-binding analog of arginine) induces in the TAR structure upon complex formation. [19][20][21][22][23] In the free form the bulged residues and the terminal A22 and U40 residues are not involved in hydrogen bonding interactions but upon arginine binding U23 and A22 sandwich arginine by forming a critical U23:A27-U38 base-triple and a A22-U40 base pair (Figure 1a, dashed red lines) and leads to a global dampening of interhelical motions.…”
Section: Introductionmentioning
confidence: 99%